2013
DOI: 10.1111/1348-0421.12092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of innate immune activation after prolonged feeding of milk fermented with three species of Lactobacilli

Abstract: The present investigation aimed at identifying the abilities of three different species of probiotic lactobacilli to modulate cellular immune responses in mouse neutrophils and macrophages in vivo over a study period of 60 days. Neutrophil respiratory burst enzymes (cytochrome c reductase and MPO) showed remarkable increased activity (P 0.01) after consumption of milks fermented by different species of probiotics over 30 and 60 days of feeding trials. Enzyme activities (b-galactosidase and bglucuronidase) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…Bacterial contaminations of the bovine uterus are almost inevitable with a prevalence of around 90% 53 with pathogenic bacteria being the main cause for the development of endometritis 54 , 55 . The immunostimulatory effects for lactobacilli were also observed in earlier studies 19 , 56 , 57 and the present study also suggests that lactobacilli are supportive for the containment of these pathogenic bacteria. It was also shown that a distinct lactobacilli strain alone or in combination with other reduced an E. coli infection and affected the pro-inflammatory reaction in bovine endometrial cells in vitro 58 , 59 .…”
Section: Discussionsupporting
confidence: 91%
“…Bacterial contaminations of the bovine uterus are almost inevitable with a prevalence of around 90% 53 with pathogenic bacteria being the main cause for the development of endometritis 54 , 55 . The immunostimulatory effects for lactobacilli were also observed in earlier studies 19 , 56 , 57 and the present study also suggests that lactobacilli are supportive for the containment of these pathogenic bacteria. It was also shown that a distinct lactobacilli strain alone or in combination with other reduced an E. coli infection and affected the pro-inflammatory reaction in bovine endometrial cells in vitro 58 , 59 .…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we assessed the release of lysosomal enzymes and NO as indicators of leukocyte functionality in neonate mice and found that PFM administration to mothers during the suckling period (BD‐PS and BD‐PS + PW) enhances their release into peritoneal fluid and supernatants of cultured macrophages, respectively, as compared with BD and vehicle (skim milk) controls. These results are in agreement with previous studies in which oral administration of probiotic‐containing ( L. casei, L. helveticus and L. paracasei ) fermented milk resulted in significant release of lysosomal enzymes (β‐galactosidase and β‐glucuronidase) and NO into both peritoneal fluid and the supernatants of activated macrophages, respectively, during short‐term (7 days) and long‐term feeding experiments with probiotics (60 days) in adult animals.…”
Section: Discussionsupporting
confidence: 92%
“…Peritoneal fluid was collected from the peritoneal cavities of mice with 5 mL of Dulbecco's modified Eagle's medium (DMEM) Ham's F12 medium following gentle massage of the abdomen as described previously by Kapila et al . . The numbers of various leukocytes in peritoneal exudate suspensions were counted on a Neubeur's chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of peritoneal macrophages is one parameter that indicates the stimulation of the systemic immune system but the mechanism used by probiotic strains is still unclear. Several authors observed the increase in the phagocytic activity of peritoneal macrophage after 2, 5 or 8 days of feeding with probiotics cultures (Kapila et al 2007(Kapila et al , 2012Rajpal and Kansal 2009), even after 60 days (Kapila et al 2013). Same effects were perceived with the probiotic Dahi culture namely DI (containing Lact.…”
Section: Effects On Macrophage Function and Leucocyte Countmentioning
confidence: 95%
“…, ; Rajpal and Kansal ), even after 60 days (Kapila et al . ). Same effects were perceived with the probiotic Dahi culture namely DI (containing Lact.…”
Section: Systemic Immune Systemmentioning
confidence: 97%